Anti-Inflammatory Potential of Some Essential Oils: A Review - Kushwah, Ritika; Gupta, M K (Asian Journal of Pharmaceutical Research and Development, 2019)
Inflammation and pain are common phenomena associated with a number of diseases. Inflammatory diseases result from the body’s response to tissue damage, and if the resolution is not adequate or the stimulus persists, there will be progression from acute inflammation to chronic inflammation, leading to the development of cancer and neurodegenerative and autoimmune diseases. It is necessary to search for new biologically active compounds with anti-inflammatory activity. Essential oils are complex mixtures isolated from aromatic plants which may possess antioxidant and anti-inflammatory activities. This article briefly summarizes the potential of essential oils and their compounds for the treatment of inflammatory diseases.